2023
DOI: 10.3389/fimmu.2023.1135834
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Clearance of longstanding, immune-deficiency-associated, vaccine-derived polio virus infection following remdesivir therapy for chronic SARS-CoV-2 infection

Abstract: The global polio eradication campaign has had remarkable success in reducing wild-type poliovirus infection, largely built upon the live attenuated Sabin oral poliovirus vaccine. Whilst rare, vaccine poliovirus strains may cause infection and subsequently revert to a neurovirulent type, termed vaccine-derived poliovirus (VDPV). Persistent, vaccine derived infection may occur in an immunocompromised host (iVDPV), where it is a recognised complication following receipt of the Sabin vaccine. This has significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Interestingly, a known, long-term (>30 years) chronic excreter appears to have stopped excreting polioviruses after COVID-19 infection and Paxlovid ™ treatment, but uncertainty remains about whether COVID-19 infection or the antiviral drug led to the end of poliovirus infection in this individual. 63 Generally, the regulatory path to approval of a specific PAVD continues to prove more challenging than might occur with the potential off-label use or repurposing of an existing antiviral or anti-enteroviral drug. The compassionate use of PAVDs for individual iVDPV excreters could potentially continue as part of studies of investigational new drugs, or could come under consideration as orphan drugs (i.e., pharmaceutical products for which insufficient markets exist to support their commercial use).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a known, long-term (>30 years) chronic excreter appears to have stopped excreting polioviruses after COVID-19 infection and Paxlovid ™ treatment, but uncertainty remains about whether COVID-19 infection or the antiviral drug led to the end of poliovirus infection in this individual. 63 Generally, the regulatory path to approval of a specific PAVD continues to prove more challenging than might occur with the potential off-label use or repurposing of an existing antiviral or anti-enteroviral drug. The compassionate use of PAVDs for individual iVDPV excreters could potentially continue as part of studies of investigational new drugs, or could come under consideration as orphan drugs (i.e., pharmaceutical products for which insufficient markets exist to support their commercial use).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified that GS-5734 inhibits RNA synthesis of EV-A71, hindering enterovirus replication, and shows broad-spectrum inhibition of a wide range of enteroviruses [ 100 ]. Similarly, current clinical data showed that vaccine-derived poliovirus infection in an immunocompromised patient was cured by GS-5734 treatment after multiple failed attempts to treat with human milk, ribavirin, and oral human immunoglobulin [ 101 ].…”
Section: Drugs Acting On 3d Polmentioning
confidence: 99%
“…A recent study reported that remdesivir treatment eliminated iVDPV in the stool of a 50-year-old patient. These results suggest that remdesivir may be effective in the treatment of iVDPV [ 139 ].…”
Section: New Strategies To Fight Against Pvmentioning
confidence: 99%